Interleukin‐4 overexpressing mesenchymal stem cells within gelatin‐based microribbon hydrogels enhance bone healing in a murine long bone critical‐size defect model. Issue 11 (14th May 2020) - Ueno, Masaya; Lo, Chi‐Wen; Barati, Danial; Conrad, Bogdan; Lin, Tzuhua; Kohno, Yusuke; Utsunomiya, Takeshi; Zhang, Ning; Maruyama, Masahiro; Rhee, Claire; Huang, Ejun; Romero‐Lopez, Monica; et al.
Abstract: Mesenchymal stem cell (MSC)‐based therapy is a promising strategy for bone repair. Furthermore, the innate immune system, and specifically macrophages, plays a crucial role in the differentiation and activation of MSCs. The anti‐inflammatory cytokine Interleukin‐4 (IL‐4) converts pro‐inflammatory M1 macrophages into a tissue regenerative M2 phenotype, which enhances MSC differentiation and function. We developed lentivirus‐transduced IL‐4 overexpressing MSCs (IL‐4 MSCs) that continuously produce IL‐4 and polarize macrophages toward an M2 phenotype. In the current study, we investigated the potential of IL‐4 MSCs delivered using a macroporous gelatin‐based microribbon (μRB) scaffold for healing of critical‐size long bone defects in Mice. IL‐4 MSCs within μRBs enhanced M2 marker expression without inhibiting M1 marker expression in the early phase, and increased macrophage migration into the scaffold. Six weeks after establishing the bone defect, IL‐4 MSCs within μRBs enhanced bone formation and helped bridge the long bone defect. IL‐4 MSCs delivered using macroporous μRB scaffold is potentially a valuable strategy for the treatment of critical‐size long bone defects.